Perception of university teaching skills from the academic and student perspective - Mendoza-Llanos, Rodolfo (2020)
A permanent challenge in higher education is the development of teaching skills in academics to respond to the new profile of the student, demanding changes in the way teaching is delivered and evaluated. Here we evaluate the perception of university teaching skills from the perspective of students and the institutional perspective provided by teachers, as well as differences by gender, in a sample of 1837 students and 227 academics from a publicuniversity in two regions of south-central Chile. The general results indicate that teachers give greater importance to skills than students. Likewise, while students value skills, generating a pleasant climate in class and innovating in work practices, academics give greater importance to the transmission of knowledge and making evaluations more flexible. Nevertheless, there is agreement between both groups, considering that planning classes is the least important competence. With respect to differences by sex, women (students and teachers) tend to give more importance to skills than men. The results point toward establishing better interpersonal relations between students and teachers beyond the classroom and above the transmission of knowledge itself, considering gender differences.